RESPON PENAMBAHAN MINERAL KALSIUM, PHOSPOR, MAGNESIUM DAN SULFUR TERHADAP KARAKTERISTIK CAIRAN RUMEN PADA TERNAK KAMBING LOKAL - Triani Adelina (State Islamic University of Sultan Syarif Kasim Riau, 2004)
Microbial growth and various fertnentation processe5in th rumen require an adequate supply of minerals. An experiment was conducted to determine rumen fluid characteristics from 20 goats of local breed. f They were randomly allocated into 4 treatments in a Randomized Block Design with 5 replication. Treatments were: A =forages (natural grasses, gIiricidia and leucaena) and concentrate (rice brand, com graL,, and coconut meal) ; B =ration A+Ca+P ; C =ration A+Ca+P+Mg and D = ration A+Ca+P+S. Ration between forages and concentrates is 60 : 40 with TDN 53.94% and CP 13.87%. The result showed that there were no effect of mineral!1Ca, P, Mg and S supplementation on the characteristics of the rumen fluid except for VFA even though it was still on the optimum condition for microbial growth. In conclusion, supplementation of Ca, P, and S was the best I among the treatments.